Pulsed laser ablation as a tool for in-situ balancing of rotating parts. (September 2016) - Stoesslein, M.; Axinte, D.A.; Bilbao Guillerna, A.
Highlights: Development of a pulse laser ablation based method for balancing rotatives. Implementation of the developed method using a fully adaptable and modular approach. Validation of the method's balancing capabilities using a real world example. Evaluation of the accuracy and precision of pulse laser ablation during laser balancing. Abstract: The balancing of complex rotating systems is a challenging task as it may require repetitive (dis)assembly to enable mass adjustments; thus, developing methods for in-situ dynamic balancing of rotatives is regarded as a key technology enabler. In this context laser balancing with its high flexibility in adjusting its firing frequency (to match that of the rotating part) and pulse energy (to vary the material removal) could offer significant advantages from both precision and cost point of view. In this paper, a laser balancing system is developed to continuously remove material from a target part in a controlled and automated manner. The amount of material ablated can be controlled by an influence coefficient, which is related to the change in vibration amplitude for a predefined amount of pulses at a given operational balancing speed, material, and geometry of the rotative part. The proposed system features a three-layered case-driven programmatic approach to optimize single-plane balancing process duration in a fully automated system. This enables the use of prioritization to avoid misfire and therefore, structural damage to the targeted part. Furthermore, the application allows the component to be balanced to all common balancing grades as specified in the ISO 1940/1 standard. Thus, validation trials involved balancing an Inconel 718 rotative to a preliminarily specified balancing grade by extracting the acceleration signals using an IIR peak filter. A computer simulation encompassing the rotor bearing state space system, a model of the laser and the adapted peak detection algorithm, has been developed and used to validate the trials conducted. Henceforth, a maximum deviation from the desired correction position of less than 1 mm has been recorded. Moreover, it has been shown that the detection and correction of imbalances can be reliably achieved by reducing the vibration level of a rotor from G 22.5 to G 19.5.